Comprehensive Physiology 1992
DOI: 10.1002/cphy.cp080231
|View full text |Cite
|
Sign up to set email alerts
|

Renin–Angiotensin–Aldosterone System and the Renal Regulation of Sodium, Potassium, and Blood Pressure Homeostasis

Abstract: The sections in this article are: Historical Background Renin Aldosterone A Coordinated Renal‐Adrenal Hormonal System: Renin, Angiotensin, and Aldosterone Comparative Aspects Brief Overview of the Renin‐Angiotensin‐Aldosterone System Biochemistry and Molecular Biology o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
29
0

Year Published

1998
1998
2020
2020

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(30 citation statements)
references
References 742 publications
1
29
0
Order By: Relevance
“…Furthermore, as we observed, such positional change generally increases the natriuresis by about 100%, to be compared with the further 400% natriuresis increase observed after NEP-I in Htx. 3,[37][38][39] Thus, both the magnitude and the time course of natriuresis after moving to the supine position, in view of the length of our baseline period, support that the further natriuresis increase observed after NEP-I is because of the drug activity. Several studies demonstrated that NEP-I, including ecadotril, has either no effect or decreases BP in normal subjects and in heart failure, renal failure, cirrhosis, and hypertensive patients.…”
Section: Study Limitationssupporting
confidence: 57%
“…Furthermore, as we observed, such positional change generally increases the natriuresis by about 100%, to be compared with the further 400% natriuresis increase observed after NEP-I in Htx. 3,[37][38][39] Thus, both the magnitude and the time course of natriuresis after moving to the supine position, in view of the length of our baseline period, support that the further natriuresis increase observed after NEP-I is because of the drug activity. Several studies demonstrated that NEP-I, including ecadotril, has either no effect or decreases BP in normal subjects and in heart failure, renal failure, cirrhosis, and hypertensive patients.…”
Section: Study Limitationssupporting
confidence: 57%
“…[23][24][25][26][27] PRA was measured with a standard radioimmunoassay technique to ensure that the hemodilution procedure (see below) had not caused a reduction in circulating blood volume, which would have stimulated renin secretion. 28 This also was ensured through measurements of RA diameter with M-and B-mode echocardiography. 29 Plasma endothelin-1 was measured with radioimmunoassay after extraction from plasma with C18 Sep-Pak Cartridges (Millipore), as described in detail elsewhere.…”
Section: Measurementsmentioning
confidence: 99%
“…Dietary sodium chloride intake is sensitively tracked by reciprocal changes in renin activity 39 and subsequently by angiotensin II and aldosterone levels. Traditionally, modulation by aldosterone of cortical collecting tubule sodium transport has been held to be important in the renal excretory response to altered dietary salt.…”
Section: Efferent Limb Of Extracellular Volume Regulationmentioning
confidence: 99%